2010
DOI: 10.2753/mer1052-8008200108
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Marketing Math Skills of Marketing Undergraduate Students Through a Unique Undergraduate Marketing Math Course

Abstract: ImprovIng the marketIng math SkIllS of marketIng undergraduate StudentS through a unIQue undergraduate marketIng math courSe gopala ganesh, Qin Sun, and Somjit BaratAlthough analytical and math abilities are among the skills that marketing undergraduates are expected to have, the extant literature indicates deficiencies in these areas. Against this backdrop, this paper describes a course that is part of the core requirements of undergraduate marketing majors at a major public university in the southwest United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Although many studies have noted the increased quantitative nature of marketing jobs (Accenture, 2014; Deloitte, 2017; LinkedIn & HubSpot, 2015; Sweetwood, 2016), studies in the marketing education literature have shown that marketing graduates often lack the quantitative skills needed for the workplace (Aggarwal et al, 2007). It is important to note that several studies in the marketing education literature have suggested methods for improving the quantitative skills of marketing students through a variety of methods such as developing proficiency in marketing metrics (Pilling et al, 2012) or learning marketing math (Ganesh, Sun, & Barat, 2010). Nevertheless, earlier studies of employers of marketing graduates have shown that employers place a greater importance on quantitative skills than students (Davis et al, 2002).…”
mentioning
confidence: 99%
“…Although many studies have noted the increased quantitative nature of marketing jobs (Accenture, 2014; Deloitte, 2017; LinkedIn & HubSpot, 2015; Sweetwood, 2016), studies in the marketing education literature have shown that marketing graduates often lack the quantitative skills needed for the workplace (Aggarwal et al, 2007). It is important to note that several studies in the marketing education literature have suggested methods for improving the quantitative skills of marketing students through a variety of methods such as developing proficiency in marketing metrics (Pilling et al, 2012) or learning marketing math (Ganesh, Sun, & Barat, 2010). Nevertheless, earlier studies of employers of marketing graduates have shown that employers place a greater importance on quantitative skills than students (Davis et al, 2002).…”
mentioning
confidence: 99%
“…Marketing students at the collegiate level have often been found to lack mathematical skills (Aggarwal, Vaidyanathan, and Rochford 2007;Ganesh, Sun, and Barat 2010). At times students have difficulties assimilating mathematical concepts and formulas to real-world scenarios such as the retail environment.…”
Section: The Challenges Of Teaching Retail Mathematicsmentioning
confidence: 99%
“…In the past, some fashion majors found themselves in marketing programs where they often perceived themselves as weaker in quantitative skills than nonmarketing majors (Newell, Titus, & West, 1996). It has been documented that students in marketing tracks often did not believe mathematics and quantitative proficiency were important in their career choice and they were more likely to avoid mathematics in their major selection (Ganesh, Sun, & Barat, 2010; LaBarbera & Simonoff, 1999). This perspective appeared to align with fashion programs housed in other fields as well.…”
Section: Review Of Literaturementioning
confidence: 99%